2000
DOI: 10.1002/1520-6874(200003/04)42:2<145::aid-tie2>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Expatriate management: Comparison of MNCs across four parent countries

Abstract: Executive SummaryThis article reports the results of a study of expatriate management and headquarters-subsidiary relations in 29 American, British, German, and Japanese multinationals and a sample of 46 of their foreign subsidiaries based on face-to-face and telephone interviews with key international HR, subsidiary HR, and subsidiary managing directors. We found that earlier studies, heavily weighted with U.S. multinationals, cannot necessarily be applied to expatriate management experiences of other nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 21 publications
4
28
3
Order By: Relevance
“…Comparative studies have suggested that there are major differences between Asian, European and North American firms with regard to subsidiary control (Almond and Ferner, 2006) and global staffing practices (Peterson et al, 2000;Tungli and Peiperl, 2009). To gain a deeper understanding of the preferred kinds of subsidiary control and the related staffing needs of MNCs from these three regions, this study examines which subsidiary control practices are implemented across MNCs from Japan, Germany and the United States.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Comparative studies have suggested that there are major differences between Asian, European and North American firms with regard to subsidiary control (Almond and Ferner, 2006) and global staffing practices (Peterson et al, 2000;Tungli and Peiperl, 2009). To gain a deeper understanding of the preferred kinds of subsidiary control and the related staffing needs of MNCs from these three regions, this study examines which subsidiary control practices are implemented across MNCs from Japan, Germany and the United States.…”
Section: Introductionmentioning
confidence: 71%
“…Already in the 1980s, Baliga and Jaeger (1984) argued that Japanese firms use more cultural control mechanisms, whereas US companies employ more hierarchical control. In line with this, Japanese organizations have consistently been identified as the most likely to staff key positions in subsidiaries with parent-country nationals (Tung, 1982;Peterson et al, 2000). Kopp (1994) and Harzing (2001) found that subsidiaries of Japanese MNCs are significantly more under expatriate control than, for example, those of German and US multinationals.…”
Section: Theoretical Contextmentioning
confidence: 99%
“…Third, this study adds to our understanding of HR in developing economies. Much research conducted on HR has focused on firms in developed economies or these firms' forays into developing economies Peterson, Napier, & Shul-Shim, 2000). More recently, HR research has started to emphasize firms in developing economies (e.g., Budhwar & Varma, 2010;Cooke & Sani, 2010;Ngo et al, 2008;Rowley & Cooke, 2010).…”
Section: Expectations Of Hr Contributions and Hr Strategic Participationmentioning
confidence: 99%
“…Instead, they find age to be an important predictor for identification. Peterson et al (1996Peterson et al ( , 2000 showed that a strong orientation towards the local subsidiary can particularly found with those HCNs who do not have international career options. Similarly, Reade (2003) finds that local managerial employees "are more likely to exert effort for the MNC as a whole if they do not perceive a nationality barrier to career mobility within the global organization" (p. 222).…”
Section: Career Aspiration and Strategic Orientationmentioning
confidence: 99%